Analisis Sistem Pengamanan dalam Menangani Overcrowding dan Konflik Warga Binaan di Lapas Kelas IIA Pekanbaru - Nasution, Rizki; Novarizal, Riky (Sisi Lain Realita Another Side Of Reality Journal Criminology, 2026)
This study aims to analyze the security system in addressing overcrowding and the potential for inmante conflict at Class IIA Pekanbaru Correctional Institution. Overcrowding in correctional institutions has become a crucial issue as it contributes to increased security and order disturbances as well as conflicts among inmates. However, studies examining security strategies to address these conditions remain limited. This study employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data were analyzed using NVivo 12 software to identify patterns and relationships among the research findings. The results indicate that the implemented security system includes preventive, repressive, and early detection strategies to address potential security and order disturbances. Nevertheless, its implementation has not been optimal due to the limited number of officers, inadequate facilities and infrastructure, and the high occupancy rate of inmates. Overcrowding has been proven to increase the potential for conflict and reduce the effectiveness of supervision. Therefore, optimizing human resources, improving security facilities, and implementing overcrowding mitigation policies are necessary to create a safer and more conducive correctional environment.